2015
DOI: 10.1039/c5ra13000j
|View full text |Cite
|
Sign up to set email alerts
|

Cu2ZnSnS4thin film solar cells with 5.8% conversion efficiency obtained by a facile spray pyrolysis technique

Abstract: A CZTS-based thin film solar cell with a powder conversion efficiency of 5.8% was obtained by using facile spray pyrolysis deposition followed by annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…As expected from the results of the Raman and XRD analyses, the Cu 2 ZnSnS 4 film obtained from the precursor solution containing stoichiometric amounts of Cu, Zn, and Sn ions (Cu concentration of 23 mmol dm −3 ) was slightly Cu‐rich. Based on the fact that the content of the Sn in the film was lower than that of the stoichiometric composition, the observed compositional deviation was caused by a reduction of the Sn component induced by evaporation during the annealing process, as discussed in our previous report . Compared to the Cu‐rich/Sn‐poor Cu 2 ZnSnS 4 film, a gradual decrease in the Cu content was observed when we used precursor solutions with Cu concentrations lower than the stoichiometric composition, whereas the Sn and Zn content (or Zn/Sn ratio) were almost constant irrespective of the change in Cu concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected from the results of the Raman and XRD analyses, the Cu 2 ZnSnS 4 film obtained from the precursor solution containing stoichiometric amounts of Cu, Zn, and Sn ions (Cu concentration of 23 mmol dm −3 ) was slightly Cu‐rich. Based on the fact that the content of the Sn in the film was lower than that of the stoichiometric composition, the observed compositional deviation was caused by a reduction of the Sn component induced by evaporation during the annealing process, as discussed in our previous report . Compared to the Cu‐rich/Sn‐poor Cu 2 ZnSnS 4 film, a gradual decrease in the Cu content was observed when we used precursor solutions with Cu concentrations lower than the stoichiometric composition, whereas the Sn and Zn content (or Zn/Sn ratio) were almost constant irrespective of the change in Cu concentration.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported the successful fabrication of solar cells with a maximum η of 5.8 % based on a Cu 2 ZnSnS 4 film deposited by a facile spray pyrolysis technique using stable aqueous precursor solutions . The use of an Sn‐rich composition of the precursor solution as well as the use of adequate post annealing at a high temperature (600 °C) for a sufficient duration (30 min) led to efficient grain growth, which is the main reason that high η values were achieved.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nguyen et al reported 5.8% power conversion efficiency for CZTS absorber‐based thin film solar cell by preparing an aqueous solution containing the nitrate form of 0.019 M copper, 0.009 M zinc, 0.0125 M tin methanesulphonate, and 0.06 M thiourea at a pH of 1.5. The grown film was annealed in the temperature range of 853 to 873 K for a duration of 10 to 50 minutes together with 20 mg of sulfur.…”
Section: Effect Of Process Parametersmentioning
confidence: 99%
“…In addition, selenization is totally avoided, thus it is environmental positive. Other routes based on nanoparticles 23 , solvothermal [24][25][26] , rotatory ball milling 27 , microwave 28 , hot-injection 25,[29][30][31][32] or non-injection methods 33 , spray pyrolisis 34 have been also applied, but with inferior effectiveness for CZTSSe production.…”
Section: Introductionmentioning
confidence: 99%